The complete guide to B2B marketing : new tactics, tools, and techniques to compete in the digital economy - King, Kim Ann (Pearson Education, 2015)
Today, B2B marketers must excel across all areas, from messaging to demand generation to sales team enablement. New technologies and techniques make excellence possible. This book makes it real. Top B2B marketer Kim Ann King will help you profit from cutting-edge B2B analytics, experimentation and optimization, marketing automation, targeting and personalization, and more. Drawing on decades of experience at pioneers such as SiteSpect, Akamai, and Open Market, she helps you assess fast-changing customers...choose your best tools and options...build a more agile, strategy-driven plan...hire the right team...drive more value from experimentation...accurately estimate spend and ROI.